Vloga laparoskopije pri kirurški obravnavi karcinoma ovarija - Jakimovska, Marina (Endoskopska revija, 2009)
Background. The role of laparoscopy in the treatment of ovarian cancer has yetto be determined. This article presents the results of laparoscopy used as the first choice surgical management in patients with clinical evidence of ovarian malignancy, admitted to the Department of Gynaecology, University Medical Centre Ljubljana in 2007 and 2008. Material and patients. Laparoscopy was proposed and performed as the primary surgical approach in 39 patients with clinical signs of ovarian malignancy. Intraoperative laparoscopic findings, surgical steps, histopathology and postoperative treatment strategy are presented. Results. Preoperatively, a suspected adnexal mass with ascites was identified in 24 patients; ascited was absent in 13 patients. In two cases, no data for the presence or absence of ascites were available. Histopathology revealed primary ovarian cancer in 33 cases and non-ovarian malignancy in six cases. According to laparoscopic staging, the patients with primary ovarian cancer were divided into two groups: a group with early-stage disease and a group with advanced ovarian cancer. In the earlydisease group (N=18) the following laparoscopic procedures were performed: adnexectomy in 13cases, cyst resection in three, omental and peritoneal biopsy in six, and collection of specimens for cytology in eight patients. In the group with advanced ovarian cancer (N=15), conversion to laparotomy was performed in fourpatients, and laparoscopic adnexectomy in 11, omental biopsy in five, peritoneal biopsy in eight, and cytology specimen collection in 11 patients. Nine patients with early ovarian malignancy were definitively managed by laparoscopy, and in eight patients laparoscopy was proposed for additional staging and treatment; one patient continued to receive chemotherapy. Among the patients with advanced ovarian malignancy, who had no intraoperative conversion to laparotomy, seven continued with chemotherapy, one underwent later laparotomy,
Keywords: Laparotomija; Ovarian Neoplasms; Jajčnik, novotvorbe; Laparoscopy; Laparoskopija; Laparotomy; Retrospektivne študije; Ascites; Ca-125 Antigen; Zdravljenje, izid; Treatment Outcome; jajčniki; tumor; Retrospective Studies; novotvorbe; karcinom; rak (medicina); kirurško zdravljenje